Pesquisa-ação em ensino híbrido: reflexões sobre uma proposta de sala de aula de inglês invertida e expandida através do Edmondo - Serafim, Valeska Favoretti (2020)
The main objective of this research is to apprehend the possibilities and challenges of a flipped and expanded English language classroom through Edmodo from the perspectives of the teacher researcher and her 27 participating students. This study was conducted in the Portuguese and English Languages course of a private higher education institution in the state of Espírito Santo, Brazil, and is characterized as an action research that follows two cycles of planning, action, observation and reflection. The first cycle refers to the preparation for flipping and expanding the English language classroom, and the second one refers to this process itself. Data were collected through annotations, Edmodo screenshots and an online questionnaire followed by a focus group interview. Regarding these last two collection instruments, they were applied to the participating students at the end of the second cycle – the 27 participating students answered an online questionnaire and nine of them were selected for a focus group interview that sought to broaden the data obtained in the questionnaire, therefore, following a mixed methodology for the completion of this study. Edmodo, a social learning network (SLN), became a fundamental tool to work with a heterogeneous group of students, especially with regard to their different levels of knowledge in English. From the teacher researcher's perspective, some of the possibilities found include expanding the classroom into cyberspace and connecting with other teachers and students of English through Edmodo. Some of her key challenges include giving attention to all participating students in face-to-face classes and spending more time planning. According to the participating students, some of the possibilities found include learning anytime and anywhere, the connection with people from other countries, and especially the division into groups according to their needs. Some of the challenges mentioned include lack of time and willingness to study in advance, technological and linguistic limitations, and the need for the teacher's physical presence to explain content